AN ANALYSIS OF THE LACK OF SOCIAL MEDIA ACCESS AND INFORMATION SERVICE BY CTC (CAWANG- TOMANG-CENGKARENG) TOLL WAY USERS IN PT JASA MARGA (PERSERO) TBK - Suparwan CK; Aang Gunawan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT Jasa Marga (Persero) Tbk is a toll way developer in Indonesia. Jasa Marga has built and opened thirteen toll ways managed by nine branches and one subsidiary company, PT. Jakarta Outer Ring Road. The length of the toll ways is 496 km or 78% of the length of toll ways in Indonesia which reached 630 km. PT. Jasa Marga, Tbk has 102 CCTV cameras and 19 cameras on Cawang-Tomang-Cengkareng toll way. Knowing the influence of social media and information service on Cawang-Tomang-Cengkareng toll way that provided by PT. Jasa Marga (Persero) Tbk was the purpose of this research. Questionnaire and field research were used in this research. The fishbone analysis was used to analyze the data. The result of this research showed that the socialization about toll road condition by social media and information service for user was not optimal. There were 14 of 30 respondents or  46.67% said Yes that they knew about the current traffic condition by social media and 13 of 30 respondent or 43.33% said Yes that they knew about the current traffic conditions by information service. Due to the lack of socialization and cooperation with mass media caused toll way users did not know about current traffic condition that made congetion on the toll way.